Private Well Water in Colorado: Collaboration, Data Use, and Public Health Outreach. (March 2015) - Brown, Eric M.; Van Dyke, Mike; Kuhn, Stephanie; Mitchell, Jane; Dalton, Hope
Abstract : As a result of participating in the Centers for Disease Control and Prevention's Private Well Initiative and Environmental Public Health Tracking Network (Tracking), the Colorado Department of Public Health and Environment was able to inventory private well water quality data, prioritize potential health concerns associated with drinking water from these wells, and create a Web portal for sharing public health information regarding private well water. The Colorado Department of Public Health and Environment collaborated with a local health department to pilot the project prior to a public implementation. Approximately 18 data sets were identified and inventoried. The Colorado Department of Public Health and Environment also participated in development and pilot testing of best practices for display of well water quality data with other Tracking states. Available data sets were compiled and summarized, and the data made available on the Colorado Tracking portal using geographic information system technology to support public health outreach regarding private wells. Abstract : This article describes collaboration, use, and public health outreach of private well water quality data in Colorado.